Linear, Edge‐Sharing Heterometallic Trinuclear [CoII–LnIII–CoII] (LnIII = GdIII, DyIII, TbIII, and HoIII) Complexes: Slow Relaxation of Magnetization in the DyIII Derivative. Issue 2 (26th November 2013) - Chandrasekhar, Vadapalli; Das, Sourav; Dey, Atanu; Hossain, Sakiat; Kundu, Subrata; Colacio, Enrique
Abstract: The sequential reaction of a multisite coordination ligand (LH4 ) with lanthanide (III) nitrates followed by the addition of Co(NO3 )2 · 6H2 O in a 4:1:2 ratio in the presence of triethylamine afforded a series of heterometallic, linear trinuclear complexes [Co2 Ln(LH3 )4 ]· 3NO3 [Ln = Dy III (1 ), Gd III (2 ), Tb III (3 ), and Ho III (4 )]. These tricationic complexes contain nitrate counteranions. The cationic portion of these complexes consists of three metal ions that are arranged in a linear fashion; a central Ln III is present between the two terminal Co II ions and is attached to the latter through two phenoxide bridging groups. This arrangement generates two contiguous four‐membered CoLnO2 rings. The Co II ions are six‐coordinate (2N, 4O) in a distorted octahedral geometry, whereas the central lanthanide ion is eight‐coordinate (8O) in a distorted square‐antiprismatic geometry. Magnetic studies of these complexes have been performed and indicate a slow relaxation of the magnetization for the Dy III derivative1 . Abstract : Linear, edge‐sharing heterometallic trinuclear [Co II –Ln III –Co II ] [Ln III = Dy (1 ), Gd (2 ), Tb (3 ), and Ho (4 )] compounds have been assembled. A slow relaxation of magnetization is observed for the Dy III derivative1 .